PENGARUH INFLASI TERHADAP YIELD OBLIGASI DAN HARGA OBLIGASI DENGAN BI RATE SEBAGAI VARIABEL INTERVENING (Studi pada Obligasi Korporasi Sub Sektor Financial Institution di BEI) - Sulistyo, Cynthia Fahmianti; Sahadati, Sadeli; Suratna, Suratna (Jurnal Paradigma, 2022)
The aims of this research is to prove the influence inflation to bond yield and bond price with BI rate as intervening variable. The data was collected from Bank Indonesia, Bursa Efek Indonesia, and Indonesia Bond Marker Directory within quartal time series during the period 2019 Q1 to 2020 Q2. The sample were all corporate bond in sub – sector financial institution with partial least square used as analysis method. Based on purposive sampling criteria was found 17 bonds using 11 issuer samples. The result from partial test showed that inflation had significant and positive effect on BI rate. Inflation and BI rate had significant and positive effect on bond yield. Inflation does not showed any significant, yet showed negatif effect to bond price. Then, BI rate and bond yield had significant and negatif effect to bond price. Inflation had significant and positive effect on bond yield through BI rate. Inflation had significant and negatif effect on bond price through BI rate.